Personal and environmental factors associated with the utilisation of maternity waiting homes in rural Zambia - Cephas Sialubanje; Karlijn Massar; Davidson H. Hamer; Robert A. C. Ruiter (BMC, 2017)
Abstract Background Although the association between the presence of maternity waiting homes (MWHs) and the personal and environmental factors that affect the use of MWHs has been explained in qualitative terms, it has never been tested in quantitative terms. The aim of this study was to test the association between the presence of MWHs and personal and environmental factors that affect the use of MWHs. Methods A cross-sectional study was conducted using an interviewer-administered questionnaire from 1st July to 31st August, 2014 among 340 women of reproductive age in 15 rural health centres in Kalomo district, Zambia. Tests of association (chi square, logistic regression analysis, odds ratio) were conducted to determine the strength of the association between the presence of MWHs and personal and environmental factors. Differences between respondents who used MWHs and those who did not were also tested. Results Compared to respondents from health centres without MWHs, those from centres with MWHs had higher odds of expressing willingness to use MWHs (adjusted odds ratio [aOR] = 4.58; 95% confidence interval [CI]:1.39-15.17), perceived more benefits from using a MWH (aOR =8.63; 95% CI: 3.13-23.79), perceived more social pressure from important others to use MWH (aOR =27.09; 95% CI: 12.23-60.03) and higher personal risk from pregnancy and childbirth related complications (aOR =11.63; 95% CI: 2.52-53.62). Furthermore, these respondents had higher odds of staying at a health centre before delivery (aOR =1.78; 95% CI: 1.05-3.02), giving birth at a health facility (aOR = 3.36; 95% CI: 1.85-6.12) and receiving care from a skilled birth attendant (aOR =3.24; 95% CI: 1.80-5.84). In contrast, these respondents had lower odds of perceiving barriers regarding the use of MWHs (aOR =0.27; 95% CI: 0.16-0.47). Factors positively associated with the use of MWHs included longer distances to the nearest health centre (p = 0.004), higher number of antenatal care (ANC) visits (p = 0.001), higher proportions of complications during ANC (p = 0.09) and women's perception of benefits gained from staying in a MWH while waiting for delivery at the health centre (p = 0.001). Conclusion These findings suggest a need for health interventions that focus on promoting ANC use, raising awareness about the risk and severity of pregnancy complications, promoting family and community support, and mitigating logistical barriers.